Efek Mediasi Kepuasan Pendengar Dalam Hubungan Kualitas Layanan Dengan Loyalitas Pendengar Radio Cassanova Bali - Ermayanti, Kadek Silvia; Suprapti, Ni Wayan Sri; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen, 2015)
In the era of modernization to globalization today, the existence of radio as marginalized. Some of the innovations made by entrepreneurs radio services have been able to restore the existence of the radio so that it remains biased greets faithful listeners. The purpose of this study was to determine the role of listener satisfaction in mediating the relationship between service quality and loyalty of listeners of Radio Cassanova Bali. The variables studied were the quality of the service, satisfaction and loyalty listener listener. The data obtained by distributing questionnaires to 105 respondents selected radio listeners by purposive sampling method. The data were analyzed using path analysis (path analysis) with the help of the Sobel test analysis techniques using SPSS. The research results show that the better the quality of services provided by Radio Cassanova Bali, the higher the level of satisfaction and loyalty Cassanova Bali Radio listeners, and listeners who have a high level of satisfaction will lead to higher loyalty on Radio Cassanova Bali. The company should further improve the quality of service for the listener the listener to feel satisfied with the services provided.
Keywords: Kualitas Layanan; Kepuasan Pendengar; Loyalitas Pendengar